MEMORY AND TIME IN VIRGINIA WOOLF'S ''ORLANDO'' - Zoidze, Natia (Online Journal of Humanities ETAGTSU, 2019)
The paper explores the major theme of Modernistic literature, namely time. The topic is examined through Virginia Woolf's distinguished novel 'Orlando''. The paper aims to show that the novel is unconventional not only due to its revolutionary narrative form but also because of its tremendous interest in time. The main goal is to emphasize the memory and time in the novel and their connection to the twentieth-century views on time. The key message is that Virginia Woolf creates the hero, Orlando who is given 300 years to live, therefore she challenges the bonds of time by gifting its hero supernatural length of life. Another striking fact which is given attention is that the main hero does not follow the Newtonian, objective time, his existence does not follow the clock time, but rather the psychological time. How does the main hero doit? With the use of memory. Memory in ‘’Orlando’’ is divided into two branches, voluntary and involuntary, the latter I suggest should be broken down into two independent types. Into outdated past and the moments of being. The main objective of the paper is to conclude that Virginia Woolf’s novel Orlando is, in fact, the representation of the ideas spread by Henry Bergson and Michel Serres. They deny the objective time and establish the notion of the subjective, psychological time where there is the duration of the moment and where the present is progressive. Full Text (PDF)